Anticipatory brain potentials in a Brain-Robot Interface paradigm - Bozinovski, A.; Bozinovska, L. (2009 4th International IEEE/EMBS Conference on Neural Engineering, 2009)
The paper describes a Brain-Robot Interface paradigm in which recognition of an anticipatory brain potential (in this case the Contingent Negative Variation-CNV) is acknowledged and reacted to by a robot arm movement. The well-known task of Towers of Hanoi is executed by a robotic arm. A measure of success is the subjects ability to generate series of CNV potentials in a CNV flip-flop paradigm which progresses towards the completion of the Towers of Hanoi task.